Asuhan Kebidanan Komprehensif Pada Ibu Hamil Ny.N Dengan Anemia Di Pmb Rungkut Surabaya - Alfi Elisa Sahidah; Fauziah.F.Hernanto; Dewi Purwatiningsih (NERSMID : Jurnal Keperawatan dan Kebidanan, 2025)
In backward countries, anemia is a common health problem. All countries must pay close attention to how they deal with this fact. It is known that anemia increases the risk of bleeding, which is a major cause of maternal death. In 2020, 4,627 mothers lost their lives in Indonesia, as reported by the Ministry of Health. The research sample used was 1 (one) pregnant woman with Anemia in the independent practice of midwife Rungkut, Surabaya. He continuity of care method is used in running parenting, which is continuous parenting starting from pregnancy, childbirth, niphas to newborns. The solutions provided are communication of information and education about nutritional needs in pregnant women, the importance of Fe in pregnancy and the impact of Hb less on pregnancy and vitamin and tablet therapy Fe. From the provided care results, that is, the difficulty can be detected immediately so that there is no gap between theory and practice and can be solved immediately so that there are no more serious problems.